2015
DOI: 10.1155/2015/315205
|View full text |Cite
|
Sign up to set email alerts
|

Lutein Has a Protective Effect on Hepatotoxicity Induced by Arsenic via Nrf2 Signaling

Abstract: Arsenic produces liver disease through the oxidative stress. While lutein can alleviate cytotoxic and oxidative injury, nuclear factor erythroid 2-related factor 2 (Nrf2) pathway plays a critical role in defending oxidative species. However, the mechanisms by which lutein protects the liver against the effect of arsenic are not known. Therefore, this study aims to investigate the mechanisms involved in the action of lutein using mice model in which hepatotoxicity was induced by arsenic. We found that mice trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 28 publications
(33 reference statements)
1
37
0
Order By: Relevance
“…Arsenic is a toxic metalloid and a potent environmental toxicant that has been reported to cause severe liver injury [1]. Humans are exposed to this metalloid through contaminated water, air, and even foods [2].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is a toxic metalloid and a potent environmental toxicant that has been reported to cause severe liver injury [1]. Humans are exposed to this metalloid through contaminated water, air, and even foods [2].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic modulates Nrf2 signaling in vivo and in vitro [46, 95, 96]. Lutein (a carotenoid) and curcumin (a diarylheptanoid) have been shown to reduce arsenic toxicity via Nrf2 activation and subsequent antioxidant gene expression [63, 64]. Additionally, in mice, curcumin promoted methylation of arsenic and accelerated its excretion [63].…”
Section: Metal Toxicity and Nrf2mentioning
confidence: 99%
“…It is highly concentrated in leafy vegetables, including Brassica oleracea and spinach, and flowers, such as Calendula officinalis. Studies have suggested that natural lutein exists in plants and it is a favorable antioxidant (7,8). Lutein prevents damage to biological membranes caused by free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Lutein prevents damage to biological membranes caused by free radicals. Due to its antioxidant functions, it has been widely employed in treating human diseases including diabetic retinopathy, fertilization and ischemia/reperfusion injury (7). However, the risks caused by inappropriate supplementation of antioxidant agents have not been investigated fully.…”
Section: Introductionmentioning
confidence: 99%